Impact of sudarshan kriya yoga on mean arterial blood pressure and biochemical parameters in medical students - Ahmad, Nisar; Hasan, Shahnawaz; Goel, Raj Kumar; Chaudhary, Lalita (International Journal of Research in Medical Sciences, 2017)
Background: Yogic life style and various yogic practices help man to strengthen his body and mind. Yogic breathing is defined as a manipulation of breath movement. The practice of yoga has beneficial effect on biochemical and physiological functions. Methods: This study was planned to see the effect of sudarshan kriya yoga on blood pressure and biochemical parameters in medical students at medical college. The study conducted on 30 medical students of age 18-21 years, at LLRM Medical College, Meerut, U.P (India) over a period of three months. Results: The result showed that yoga had beneficial effect on blood pressure, blood glucose level and cholesterol level. The mean blood pressure shows highly significant reduction after 3 months of yoga practice. It was also found that there is significant improvement in Lipid Profile parameters after sudarshan kriya yoga practices. Conclusions: Living a happy and healthy life on all planes is possible through the unified practice of sudarshan kriya yoga (SKY) along with asana and pranayam. The practice of SKY seems to be beneficial on mean blood pressure and biochemical parameters in normal healthy individuals. This unique breathing practice is a potent energizer.